2014
DOI: 10.1002/ajim.22299
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease and cancer mortality in a cohort of workers exposed to vinyl chloride, carbon disulfide, rotating shift work, and o‐toluidine at a chemical manufacturing plant

Abstract: Background We updated through 2007 the mortality experience of 1,874 workers employed at a New York State chemical manufacturing plant between 1946 and 2006. Methods Reassessed exposures to vinyl chloride, carbon disulfide, and shift work and categories of o-toluidine exposure were based on year, department and job title. Standardized mortality ratios (SMR) compared mortality to that of the US population. Internal comparisons used directly standardized rate ratios. Results Hepatobiliary cancer mortality wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Contamination of groundwater with chemicals such as trichloroethylene (TCE), cadmium, lead, nickel, thallium, and arsenic, and human exposure to organic solvents like toluene, benzo[a]pyrene, and dioxin, and xylene have been shown to increase the risk of HCC . Occupational exposure to chemicals like dichlorodiphenyl trichloroethane (DDT) and nitrosamines is another risk factor for HCC .…”
Section: Environmental Toxinsmentioning
confidence: 99%
“…Contamination of groundwater with chemicals such as trichloroethylene (TCE), cadmium, lead, nickel, thallium, and arsenic, and human exposure to organic solvents like toluene, benzo[a]pyrene, and dioxin, and xylene have been shown to increase the risk of HCC . Occupational exposure to chemicals like dichlorodiphenyl trichloroethane (DDT) and nitrosamines is another risk factor for HCC .…”
Section: Environmental Toxinsmentioning
confidence: 99%
“…Few studies have reported a significant prevalence of lung cancer [13], adrenal gland angiosarcoma [14], and brain injury [15] among exposed workers. In addition, VC results in a 10-fold increase in hepatobiliary cancer mortality and a 13-fold increase in mortality in those exposed to VC for more than 16 years [16]. The relative risk of hepatocellular carcinoma increases in a similar pattern with angiosarcoma of the liver among exposed workers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hyung-Joon Jhun et al suggested that CS 2 poisoned subjects have an increased risk of ECG abnormalities even after the exposure to CS 2 is no longer present [ 27 ]. Several cross-sectional epidemiological studies have demonstrated that exposure to CS 2 can result in increased cardiovascular risk factors and thus mortality [ 9 11 , 28 ]. Recently, long-term exposure to CS 2 was found to be an independent risk factor for changes in intima-media thickness in a German rayon manufacturing plant [ 9 ].…”
Section: Discussionmentioning
confidence: 99%